Introduction: Rethinking Spain From Across the Seas - Jill Robbins; Roberta Johnson (Studies in 20th & 21st Century Literature, 2006)
For much of the twentieth century, critical studies of "Peninsular Spanish Literature" largely followed a generational paradigm that stressed the peculiarities of Spanish history and texts written by Spanish men in the Castilian language, thereby circumscribing the literary within the boundaries of a specific form of national identity...
Keywords: Peninsular Spanish literature; Spain; Spanish history; Castilian; modernity; Iberian cultura movements; trans-atlantic modernity; belatedness; historicity; time; postcolonial theory